2016
DOI: 10.1080/15685551.2016.1152540
|View full text |Cite
|
Sign up to set email alerts
|

Groundnut oil based emulsion gels for passive and iontophoretic delivery of therapeutics

Abstract: There is a persistent demand for an efficient drug delivery system, suitable for the delivery of both hydrophilic and lipophilic drugs. This study explores groundnut oil-based emulsion gels for the above-mentioned application. On the basis of stability, two representative gels OG5-80 (low oil content) and OG7-45 (high oil content) were studied further. Analysis of microarchitecture by ESEM and confocal microscopy, in conjugation with fluorescence recovery after photobleaching, confirmed the conversion of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…According to Table 1, the antibacterial, antifungal and antiviral activities of all emulgels which were studied were good, and few studies reported greater activity than the existing marketed products [25,33]. Emulgels formulated effectively delivered hydrophobic and less water soluble drugs like metronidazole, ciprofloxacin, terbinafine and ketoconazole to the targeted site [25,27,28,29,31]. Most of the formulations showed a good in vivo therapeutic response with reduced systemic toxicity [23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Table 1, the antibacterial, antifungal and antiviral activities of all emulgels which were studied were good, and few studies reported greater activity than the existing marketed products [25,33]. Emulgels formulated effectively delivered hydrophobic and less water soluble drugs like metronidazole, ciprofloxacin, terbinafine and ketoconazole to the targeted site [25,27,28,29,31]. Most of the formulations showed a good in vivo therapeutic response with reduced systemic toxicity [23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…The common problem encountered during the development of new formulations is the hydrophobic nature of the drugs, which leads to solubility and bioavailability problems [9] .Therefore, hydrophobic drugs, can be added into the oil phase of the emulsion and delivered to the skin as an emulgel formulation where gels are not suitable dosage forms in delivering hydrophobic drugs. These characteristics of emulgel make them a more effective dosage form [25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of relaxation is determined by the elasticity index. Hydrogels with a higher %R are characterized by lower stiffness [ 50 , 51 ]. The highest %R value was recorded for the H3-INS formulation (72.7%, T = 25 °C; 74.9%, T = 32 °C).…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of relaxation is determined by the elasticity index. Hydrogels with a higher %R are characterized by lower stiffness [50,51]. The highest %R value was recorded The percentage of relaxation is determined by the elasticity index.…”
Section: Resultsmentioning
confidence: 99%
“…The model hydrophilic drug (metronidazole, 0.2 g) was mixed to the homogeneous mixture. The hot emulsion was then cooled down to room temperature in order to induce gelation [13].…”
Section: Development Of Mobile App For Communicating With the Iontophmentioning
confidence: 99%